Pengalaman Auditor Sebagai Pemoderasi Pengaruh Time Budget Pressure Pada Kualitas Audit - Budiadnyani, Ni Putu (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study examines the effect of time budget pressure on audit quality. In addition, this study also examines the ability of the auditor's experience as a moderating variable. The number of samples analyzed was 65 auditors who worked at a registered public accounting firm in Denpasar. Determination of the sample in this study using purposive sampling with the criteria of an auditor who has at least one year's experience. The analysis technique used is linear regression and Moderated Regression Analysis (MRA). The results of the analysis show that time budget pressure has no effect on audit quality. Auditor experience is able to weaken the effect of time budget pressure on audit quality.